A new surface heat flow map of the Northern Apennines between latitudes 42.5 and 44.5 N. (September 2019) - Pauselli, C.; Gola, G.; Mancinelli, P.; Trumpy, E.; Saccone, M.; Manzella, A.; Ranalli, G.
Highlights: A revised surface heat flow map of a sector of the Northern Apennines is presented. The map is constrained by logs from 174 wells drilled for geothermal and hydrocarbon exploration purposes. The results confirm that the 70 mW m −2 isoline corresponds to a major tectonic boundary of the region. Abstract: A revised surface heat flow map of a sector of the Northern Apennines is presented, constrained by recently available thermal and petrophysical logs from 174 wells drilled for geothermal and hydrocarbon exploration purposes. The borehole temperatures have been corrected for drilling, inclination, and palaeoclimate effects. The corrected temperature data, combined with petrophysical parameters for each individual formation, have been used to derive shallow geotherms (down to a maximum depth of 8 km), which have yielded site-specific heat flow values. These values, once corrected for palaeoclimatic topographic and erosion/sedimentation effects, have been contoured by a kriging procedure to obtain the heat flow map. The map shows a clear distinction between a western zone (the Tyrrhenian Domain) of high heat flow (>150 mW m −2 ), with closely spaced heat flow isolines, and an eastern zone (the Adriatic Domain) of relatively low (<70 mW m −2 ), spatially uniform heat flow. The boundary between the two zones is roughly parallel to the axis of the Apennines. Five crustal geotherms (extending to the Moho) and the corresponding rheological profiles confirm that the 70 mW m −2 isoline corresponds to a major tectonic boundary, across which the thermal, structural, and seismic properties of the lithosphere go through a significant change.